Effect of Head Teachers’ Collaborative Partnerships on Inclusive Education Implementation in Public Primary School - Shiwani, Douglas; Akala, Winston; Kalai, Jeremiah; Gatumu, Jane (Jurnal Educative: Journal of Educational Studies, 2021)
The purpose of the study was to investigate the effect of head teachers’ collaborative partnerships with parents, government agencies and NGOs, on the implementation of inclusive education in public primary schools in Nairobi City County in Kenya. Descriptive survey was applied, and Chi-square tested the null hypothesis. Questionnaires were administered to 71 head teachers and 297 teachers, supplemented by document analysis. Interview was used on eight Quality Assurance Standards Officers (QASOs) and four Education Assessment Resource Centre Officers (EARCs). Quantitative data was coded and analysed using descriptive statistics, and presented in frequency tables and bar graphs. Qualitative data was coded, transcribed and presented in narrative form. The study established the relationship between head teachers’ collaborative partnerships with implementation of inclusive education. Nevertheless, majority of schools lacked well- structured coordinated partnerships resulting in low participation in schools programs as referenced by head teachers and teachers on provision for specialized teaching and learning resources, 63.4% and 63.3%; assessment of learners, 64.8% and 70.4%; outsourcing of funds, 69% and 69.7%. Therefore, head teachers should increase capacities in collaborative partnerships and fully utilize them for inclusive education implementation.Penelitian ini bertujuan untuk mengetahui pengaruh kemitraan kolaboratif kepala sekolah dengan orang tua, lembaga pemerintah dan LSM, pada pelaksanaan pendidikan inklusif di sekolah dasar negeri di Kota Nairobi di Kenya. Survei deskriptif diterapkan, dan Chi-square menguji hipotesis nol. Kuesioner diberikan kepada 71 kepala sekolah dan 297 guru, dilengkapi dengan analisis dokumen. Wawancara digunakan pada delapan Petugas Standar Penjaminan Mutu (QASO) dan empat Petugas Pusat Penilaian Pendidikan (EARC). Data kuantitatif diberi kode dan dianalisis menggunakan statistik deskriptif, dan disajikan dalam tabel frekuensi dan grafik batang. Data kualitatif dikodekan, ditranskripsikan dan disajikan dalam bentuk naratif. Studi ini menjelaskan hubungan antara kemitraan kolaboratif kepala sekolah dengan implementasi pendidikan inklusif. Namun, sebagian besar sekolah tidak memiliki kemitraan terkoordinasi yang terstruktur dengan baik, yang mengakibatkan rendahnya partisipasi dalam program sekolah seperti yang dirujuk oleh kepala sekolah dan guru tentang penyediaan sumber untuk belajar dan mengajar, 63,4% dan 63,3%; penilaian peserta didik, 64,8% dan 70,4%; outsourcing dana, 69% dan 69,7%. Oleh karena itu, kepala sekolah harus meningkatkan kapasitas dalam kemitraan kolaboratif dan memanfaatkannya sepenuhnya untuk pelaksanaan pendidikan inklusif.